Controlled synthesis of TiO2 using a combined sol gel and dielectrophoresis method. Issue 20 (28th May 2015) - Cui, Chenyang; Chen, Huiying; Lan, Bihao; Zhang, Lu; Ma, Rui; Geng, Junfeng; Li, Hua; Hu, Jing
<x xml:space="preserve">Abstract</x> A combined sol–gel and dielectrophoresis method could achieve controlled preparation of TiO2-NPs with uniform size, and the catalytic activity of TiO2 using this method is higher than that produced by using sol–gel only.